2005
DOI: 10.1002/jnr.20727
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline attenuates white matter damage in a rat model of chronic cerebral hypoperfusion

Abstract: White matter lesions are thought to result from chronic cerebral ischemia and constitute a core pathology of subcortical vascular dementia. This rarefaction has been known to be associated with microglial activation. We investigated whether minocycline, a microglial inhibitor, attenuates the white matter damage induced by chronic cerebral hypoperfusion that is used as a model of vascular dementia. Male Wistar rats were subjected to bilateral, permanent occlusion of the common carotid arteries (BCCAO) to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 23 publications
(32 reference statements)
0
61
0
Order By: Relevance
“…Moreover, chronic cerebral hypoperfusion leads neuronal damage not only in the hippocampus but also in the cortex (Shibata et al, 2004;Cho et al, 2006;Ueno et al, 2009). In present research, we observed the protective effects of LIG on both parietal cortex and hippocampus of 2VO rats.…”
Section: Introductionmentioning
confidence: 54%
“…Moreover, chronic cerebral hypoperfusion leads neuronal damage not only in the hippocampus but also in the cortex (Shibata et al, 2004;Cho et al, 2006;Ueno et al, 2009). In present research, we observed the protective effects of LIG on both parietal cortex and hippocampus of 2VO rats.…”
Section: Introductionmentioning
confidence: 54%
“…It is known to control the breakdown of MBP (Chandler et al, 1995), a late component of myelin formation that is produced by Schwann cells in injured peripheral nerve (Gupta et al, 1988;LeBlanc and Poduslo, 1990). While MMP-9-dependent degradation of MBP has been shown in models of multiple sclerosis (Gijbels et al, 1993;Proost et al, 1993) and cerebral ischemia (Asahi et al, 2001;Cho et al, 2006), this is the first demonstration of this relationship in the PNS. Other MMPs, such as MMP-12 (Larsen et al, 2006) andMMP-3 (D'Souza andMoscarello, 2006), regulate MBP processing in the CNS and may play a role in peripheral nerve.…”
Section: Discussionmentioning
confidence: 92%
“…Several authors have shown that the long-lasting learning deficits observed in these rats are at least partially attributable to damage to the white matter (Zhang et al, 2011). Cho et al (2006) identified that the main areas affected are corpus callosum, optic tract, and internal capsule in rats with chronic cerebral hypoperfusion. Experimental evidence demonstrated the initiating role of chronic cerebral hypoperfusion in neural damage to the white matter (WM) areas and the visual system.…”
Section: Discussionmentioning
confidence: 98%